2019
DOI: 10.1038/s41598-019-50277-y
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 is Expressed by Ameloblasts, Cleaves the RELT TNF Receptor Extracellular Domain and Facilitates Enamel Development

Abstract: MMP20 cleaves cadherins and may facilitate cell movement, however MMP20 is not known to cleave tight junction or desmosome proteins. Ameloblasts had not previously been screened for membrane anchored proteases that could contribute to cell movement. Here we performed a PCR screen for proteolyticlly active A Disintegrin And Metalloproteinase (ADAM) family members. These proteinases are termed sheddases because they have a transmembrane domain and their catalytic domain on the cell surface can function to releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The sTNF-α forms homotrimers to recognize TNFR to regulate immune response [ 59 , 60 ]. TNFR has also been identified as a substrate for ADAM10 [ 54 ], and the current study shows that ADAM17 cleaved TNFR-1 as well of microglial cells. IL-6 binds to IL-6R to trigger an immune response, and during this process IL-6 signaling needs the involvement of membrane-bound IL-6R to form the IL-6/IL-6R/gp130 complex [ 61 ].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The sTNF-α forms homotrimers to recognize TNFR to regulate immune response [ 59 , 60 ]. TNFR has also been identified as a substrate for ADAM10 [ 54 ], and the current study shows that ADAM17 cleaved TNFR-1 as well of microglial cells. IL-6 binds to IL-6R to trigger an immune response, and during this process IL-6 signaling needs the involvement of membrane-bound IL-6R to form the IL-6/IL-6R/gp130 complex [ 61 ].…”
Section: Discussionsupporting
confidence: 59%
“…These results indicate that p CS might negatively affect the innate immune response of BV2 microglia through inhibiting ADAM17, and possibly through ADAM10. Given that ADAM10 and ADAM17 cleave TNF-α and other cytokine-related substrates, such as IL-6 receptor (IL-6R) and Tumor necrosis factor receptor 1 (TNFR-1) [ 52 , 53 , 54 ], we further investigated the potential role of ADAM10 and ADAM17 in innate immune and phagocytotic responses of BV2 microglial cells constitutively and after LPS stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…These similarities of expression staging and phenotype could suggest a possible common mechanism for these different forms of AI. Of note is the recent report that ADAM10, a protein known to release anchored proteins, is expressed during the secretory phase of amelogenesis (but not thereafter) and that ADAM 10 cleaves the extracellular domain of RELT . Lamellal structures were not present in murine Relt −/− enamel, although there was an absence of the poorly mineralised spaces that would normally be expected at the dentino‐enamel junction.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, it was recently shown that Notch1 -expressing cells in the stratum intermedium represent a reservoir of dental epithelial progenitors that are activated upon tooth injury and contribute to the regeneration of the ameloblast layer ( Sharir et al., 2019 ). Adam10 expression in ameloblasts was recently reported, and in vitro results suggested a role for this molecule in the regulation of enamel secretion ( Ikeda et al., 2019 ).…”
Section: Introductionmentioning
confidence: 87%